Non-stationary response of Pacific saury (Cololabis saira) in the northwestern Pacific to climate variability - Cao, Chang; Ma, Shuyang; Liu, Yang; Tian, Hao; Liu, Shigang; Li, Jianchao; Tian, Yongjun (Frontiers in Marine Science, 2025)
Pacific saury (Cololabis saira) is a typical small pelagic fish in the northwestern Pacific with considerable fluctuations in productivity, bringing about great economic and ecological concerns. Numerous studies have suggested that the population dynamics of Pacific saury is an integrated process affected by multiple environmental and climatic drivers. However, little has hitherto been done to incorporate the non-stationary effects of multiple drivers, impeding progress in the understanding of the population dynamics and the development of management strategies. In this study, we adopted multivariate statistical analyses such as variable coefficients generalized additive models to determine the non-stationary effects of climatic and environmental variations on the population dynamics of Pacific saury. The results showed that Pacific saury populations in the northwestern Pacific responded to the climate regime shifts in the late 1980s and early 2000s. Non-stationarity was identified in the relationships between climate/environment and Pacific saury. The dynamics of Pacific saury from 1970 to 2021 could be divided into four periods: the 1970s and 1980s when the Siberian High and the intensification of the East Asian winter monsoon drove down the water temperature, providing a suitable habitat and resulting in an increase in resource abundance; In the 1990s, the rise in temperature led to a reduction in resource abundance; At the beginning of the 21st century, the enhancement of the Siberian High brought about a suitable habitat, and the resource abundance showed a significant increase; The unfavorable high water temperature environment in the 2010s caused the resource abundance to decrease once again. This study highlights that precise identification of the population status and climatic conditions is helpful to achieve good trade-offs between resource exploitation and protection and to facilitate ecosystem-based management for Pacific saury fisheries.